CLINICAL OUTCOMES OF MONO-THERAPY VERSUS DUAL ANTIHYPERTENSIVE THERAPY IN PATIENTS PRESENTING AT TEHSIL HOSPITAL IN PAKISTAN - HUSSAIN, J; ALTAF, R; SHAKOOR, A; ASHRAF, M; MANSHA, I; ASIM, F (Biological and Clinical Sciences Research Journal, 2024)
Hypertension, a prevalent and potentially life-threatening condition, remains a significant public health concern in Pakistan. This article aims to investigate and compare the clinical outcomes of antihypertensive monotherapy versus combination therapy in patients treated at Tehsil Hospital, a critical healthcare facility in the Tehsil region of Pakistan. Objective: To assess and compare the clinical outcomes of hypertensive patients treated with monotherapy and those receiving a combination of antihypertensive medications at Tehsil Hospital, Pakistan. Methods: The study was carried out at Tehsil Hospital, Punjab-Pakistan. All adult participants (30 ≥ and ≤70 years) who were on antihypertensive medicine for at least 6 weeks and were diagnosed as hypertensive (average blood pressure of >140/90 mm Hg on at least two clinic visits) were included in the study from April 11 to June 20, 2022. The data was analyzed by SPSS 20. Statistical tests like chi-square were applied to obtain the required results. Results: A total of 136 study subjects were enrolled. Out of these, 113(81%) were male subjects, 23(17%) were female, 12(17.6%) smokers, and patients suffering from chronic liver disease were as 26(38.2%) treated with mono-therapy as compared with dual therapy with significant p-value 0.00 and 0.001. Other co-morbidities like the previous history of IHD, DM, and chronic kidney disease were treated with both therapies with insignificant p-values as > 0.05. Clinical outcomes were observed, and it was shown that more patients with stroke were treated with mono-therapy as p-value > 0.05 while comparing with major bleeding and control of hypertension showed a significant p-value of <0.05. Conclusion: Treatments in combination are effective and advised. The most important element in the management of hypertension, irrespective of whether medication is utilized, the goal is to get blood pressure down to the desired amount. Effective communication is essential for doctors, other healthcare professionals, and patients to treat patients.